Pengaruh Pemberian Madu Terhadap Penurunan Nyeri Pasca Imunisasi Measles Rubella - Sumantri; Rini Rahayu; Ari Kurniarum (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: children after being given Measles Rubella (MR) immunization often experience pain in the injection area and parents become confused and panicked. Various efforts, both using drugs and traditional methods, are carried out to reduce pain. One of the traditional methods is by giving children honey to drink. This study aims to determine the effect of giving honey on reducing pain after MR immunization in children aged 9-18 months in the Trucuk I Klaten Health Center area.Method: The research method used is analytical observational, namely researchers try to find the influence between variables by conducting an analysis of the data collected and using a quasi-experimental one group pretest-posttest research design.Result: The results of the study on 20 respondents showed mean pain score after MR immunization before the honey solution drink (pre-test) 5.20; standard deviation 1,765 and mean pain score after the honey solution drink (post-test) 2.70; standard deviation 1,174. The results of the Paired Sample t Test analysis showed a sig value (2-tailed) of 0.000 < 0.05. It can be concluded that post-MR immunization pain in children aged 9-18 months will decrease after drinking honey solution and the decrease in pain scoreis significant.Keywords: Honey, Pain, Immunization, Measles Rubella